Answer:
-1, -9
Step-by-step explanation:
Given the expression;
![x^2+10x+9=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/30riv5rewqrqwvujdq8y29wvdg32swo2uo.png)
To apply the completing the square method;
First, subtract 9 from both sides
![\begin{gathered} x^2+10x+9-9=0-9 \\ x^2+10x=-9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/yjth8gapkanj2fzm3f2hqn3c954epg0yml.png)
Complete the square by adding the half of the square of the coefficient of x to both sides of the expression as shown;
![\begin{gathered} x^2+10x+((10)/(2))^2=-9+((10)/(2))^2 \\ x^2+10x+(5)^2=-9+(5)^2 \\ (x+5)^2=-9+25 \\ (x+5)^2=16 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/d0b0bdptl58dg5kk0irx6hwj6nkeglt0qf.png)
Next is to find the values of x by squaring both sides of the expression;
![\begin{gathered} \sqrt[]{(x+5)^2}=\pm\sqrt[]{16} \\ x_{}+5=\pm4 \\ x+5\text{ = 4 and x+5=-4} \\ x\text{ = 4-5 and x = -4-5} \\ x\text{ = -1 and x =-9} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rhs936mvc8oc6chise2edt6zusv4ph2byh.png)
Hence the values of x are -1 and -9